Karakteristik Fisikokimia dan Organoleptik Biskuit Tepung Ubi Jalar Ungu dan Tepung Koro Pedang Putih - Khafsah, Fatya N; Yanti, Rini; Manikharda, Manikharda (Universitas Pattimura, 2024)
Biscuits were made of purple sweet potato flour and jack bean flour as an effort to add nutritional value to the biscuits. This study aimed to determine the effect of different substitution ratios of purple sweet potato flour and jack bean flour on the chemical, physical, and organoleptic characteristics and their benefits as alternative foods for the daily nutritional needs of stunting toddlers. In this study, we used an experimental method with a ration of purple sweet potato flour and jack bean flour. It consisted of four levels treatment P1 (58%:42%); P2 (67%:33%); P3 (75%:25%); and control (100%:0%). The biscuit acceptability test for the four biscuit formulas was carried out using the hedonic test. The selected formula was determined based on the preferences of 70 untrained panelists. Based on the results of the study, it was found that P3 biscuits with the ratio of purple sweet potato flour: jack bean flour (75%: 25%) was the most preferred formula and had a moisture content of 3.41%, ash 2.24%, fat 25.39%, protein 3.94%, carbohydrates 68.42%, total energy 518.03 kcal/100 g; and a hardness value of 12.85 N. The overall acceptance test for P3 biscuits obtained a value of 4.51 (rather like). As a snack, biscuits with the selected formula can meet 9% of protein needs, 26% of fat needs, and 15% of daily carbohydrate needs for toddlers aged 1-3 years and provide energy of 238 kcal/100 g by consuming 14 pieces of biscuits or the equivalent of 46 g of biscuits.